A STUDY ON THE ABILITY OF THE FOURTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM IN UNDERSTANDING ENGLISH POETRY - Fitriani, Fitriani; Delfi, Syofia; Dahnilsyah, Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to find out the ability of the fourth semester students of English Study Program FKIP UR in understanding English poetry. The number of sample was 40 students of the fourth semester students of English study program FKIP UR which was decided by using the Cluster Random Sampling technique. The data were collected by administering written test where the students are obliged to write general and detailed meaning based on the given poetry. The students’ scores were scored by three raters and were classified into five levels of ability, which are very poor, poor, mediocre, good and excellent. Based on research findings, it was found out that the ability of fourth semester students was at mediocre level with average score of 60. Besides, it was also found that the students’ ability in the content aspect was higher than the language-structures aspect where the average score of contents is 3,03 while the average score of language-structures is 2,93. This research implies that the fourth semesters of English study program were able to understand English Poetry.Key Words: Study, Ability, Understanding, Poetry Mastery